FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA GURU SMKS DAN SMAS SANDIKTA BEKASISELAMA PEMBELAJARAN DARING TA 2020-2021 - Vira Kurniati (2021)
Occupational stress is a condition that may caused psychological and physical disorders due to inappropriate capacity and pressure at work. Teachers as part of the workforce, are inseparable from these, especially in the change of teaching methods to online learning systems during the COVID-19 pandemic. This study was conducted to determine factors related to occupational stress among teachers in SMKS and SMAS Sandikta Bekasi during the online learning process in 2020-2021. This research was a quantitative analytic research design with a total sampling technique (59 respondents). The research instruments was a ISMA Stress Questionnaires that distributed with google form. The univariate analysis results found that 61% teachers experienced heavy occupational stress. The results of the multivariate analysis showed there was an increased risk of stress in teachers with heavy workloads (POR = 6,846, 95% CI: 1,593-29,427), unfaithful working-environment (POR = 6,404, 95% CI: 1,410-29,085), prolonged length of employment (POR = 4,569, 95% CI: 1,167-17,892), and age 45-60 years (POR = 4,322, 95% CI: 1,041-17,951). It is recommended that respondents do time management, relaxation, enjoying entertainment, and exercise. It is expected for SMKS and SMAS Sandikta Bekasi to be able to carry out counseling, conduct training, and provide appropriate task sharing.